Food Security Analysis of Dairy Farmers’ Households in Getasan District of Semarang Regency - Wijayanti, Nur Rini; Gayatri, Siwi; Mariyono, Joko (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
Food security is a problem that cannot be ignored, because food security is closely related to the problem of hunger and poverty, which is a problem for all countries in the world. One way to end hunger is to achieve food security from each individual. Food security status of a region depends on the food security of households in the region. This study was aim to analyze the status of food security of dairy farmers' households in Getasan District, Semarang Regency. The method used was a survey method with multiple stage sampling with cluster sampling as a determination of the location of research. The determination of respondents was carried out randomly at a predetermined location. The total respondents taken in this study were 102 respondents who were households of dairy farmers and wives who had cattle 2-6 heads. The data analysis method used was quantitative descriptive analysis, using calculation formulas and cross classification tables between two food security indicators, namely the share of food expenditure and the level of household energy consumption per capita per day. The study result showes that the average percentage of per capita energy consumption per day was 78.7791% and the average percentage share of food expenditure was 62.6404%. While the results shows that the level of food security was dominated by households with food vulnerable status. The advice that can be given to overcome this situation is to increase counseling, training and assistance to the housewives regarding nutritious food information and how to fulfill food independently, such as home gardening.